Pelatihan Pencatatan Keuangan Pelaku UMKM Rewulu Kulon Sidokarto Godean Sleman D.I Yogyakarta - Nanang Epriyanto, Tri; Wulandari, Ika (Universitas Gajah Putih, Indonesia, 2023)
KM plays a role in building the national economy, namely absorbing job seekers, raising income, building rural economy, increasing non -gas exports and increasing gross domestic product (GDP). However, not all UMKM actors record transactions in bookkeeping. This service activity aims to provide training in the preparation of simple financial statements of UMKM actors. The training subjects were UMKM actors in Rewulu Kulon Sidokarto Godean Sleman. The method used is the lecture method, tutorial and discussion. This activity was carried out on 6 and 13 May 2023 involving 20 participants. Participants are given training on financial recording. Training activities for the preparation of simple financial statements in Rewulu Kulon Sidokarto Godean Sleman went smoothly. Post -training, knowledge and skills of participants in preparing financial statements increases. Increasing the ability to prepare financial statements helps UMKM actors in calculating the benefits or losses of business cash flows and flows.